THE EFFECT OF DISCIPLINEAND WORK MOTIVATION ON THE PERFORMANCE OF PT GADING PRIMA PERKASA EMPLOYEES - Yenni Arnas; Ika Endrawijaya; Yhonanda Harsono; Anton Bagus Wicaksono (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This study aims to examine the effect of discipline and work motivation on employee performance at PT. Gading Prima Perkasa. The variables used in this study are Discipline, Work Motivation and Employee Performance. The population of this study were all employees of PT. Gading Prima Perkasa as many as 60 people. The sampling technique is a saturated sample technique, the entire population is sampled. The analysis used is multiple linear regression analysis to see the effect of the independent variables on the dependent variable either jointly or individually. Hypothesis testing using the feasibility test model (F test and t test) is said to be feasible to measure the independent variables, namely Discipline and Work Motivation on the dependent variable of Employee Performance. Work discipline has a positive and significant effect on employee performance, it can be proven from the tcount 2.108 > from the ttable value 1.671 with a significance value of 0.039 from the t-table value of 1.671 with a significance value of 0.006 Ftable value of 3.15 with a significant value of 0.000